User Experience Analysis on Customer Satisfaction in Using Mobile Banking Application at PT. Bank Syariah Indonesia - Siregar, Rezkika Gusmiranda; Wibowo, Rulianda Purnomo; Rini, Endang Sulistya (Journal Analytica Islamica, 2025)
This study aims to analyze the influence of user experience and e-service quality on customer satisfaction in the context of mobile banking services at PT. Bank Syariah Indonesia (BSI). The research focuses on how user interaction with the BSI Mobile application and the perceived quality of electronic services affect customer satisfaction directly and indirectly. To achieve these objectives, the study employs Structural Equation Modeling using Partial Least Squares (SEM-PLS). The validity and reliability of the constructs were tested through convergent validity, discriminant validity (using cross loading and Heterotrait-Monotrait Ratio), and internal consistency measures such as Cronbach's alpha and Average Variance Extracted (AVE). The structural model was assessed using R-square, path coefficients, and t-statistics for hypothesis testing. The findings reveal that user experience has a significant direct influence on customer satisfaction (t = 2.697, p = 0.007), while e-service quality also has a significant and stronger effect on customer satisfaction (t = 7.353, p = 0.000). Furthermore, e-service quality mediates the relationship between user experience and customer satisfaction significantly (t = 7.402, p = 0.000), indicating that a better user experience enhances perceived service quality, which in turn leads to higher customer satisfaction. The study concludes that both user experience and e-service quality are critical determinants of customer satisfaction in digital banking services. Managerially, this suggests that continuous improvement in user interface design and e-service features can significantly enhance customer satisfaction and strengthen customer loyalty in the highly competitive Islamic banking industry.